Income generation of PAYG pension system - Nasibova, O. (Державний торговельно-економічний університет, 2014)
The article discloses some tools of income generation in PAYG system, determines special aspects of income determination in Ukrainian Pension Fund. It studies the components and the structure of earnings to the system of the first level pension insurance for 2000–2013. The main problems and lacks in income generation of Ukrainian Pension Fund were indicated.

Збільшення Пенсійного фонду є одним з най важливіших аспектів соціального захисту населення України. Постійне зрос тання соціальних стандартів на етапі реформування економіки вимагає збільшення доходів, які забезпечать потреби непрацездатного населення.
Формування дохідної частини солідарної системи пенсійного страхування
Keywords: pension insurance; Ukrainian Pension Fund; own profits; transferred profits; pension coverage; income; пенсійне страхування; Пенсійний фонд України; власні прибутки; які трансформуються в дохід; пенсії; прибутки